Impact of oral corticosteroids on respiratory outcomes in acute preschool wheeze: a randomised clinical trial. Issue 4 (16th October 2020) - Wallace, Alexandra; Sinclair, Owen; Shepherd, Michael; Neutze, Jocelyn; Trenholme, Adrian; Tan, Eunicia; Brabyn, Christine; Bonisch, Megan; Grey, Naomi; Johnson, David W; McNamara, David; Thompson, John M D; et al.
Abstract : Objective: To determine if administration of oral prednisolone to preschool children with acute wheeze alters respiratory outcomes. Design: Double-blind, randomised, placebo-controlled equivalence trial. Setting: Three hospitals in New Zealand. Patients: 477 children aged 24–59 months with acute wheeze associated with respiratory illness. Interventions: 2 mg/kg (maximum 40 mg) oral prednisolone or similar placebo, once daily for 3 days. Main outcome measures: Primary outcome was change in Preschool Respiratory Assessment Measure (PRAM) score 24 hours after intervention. Secondary outcomes included PRAM score at 4 hours, length of emergency department and inpatient stays, admission and representation rates, time to return to normal activities and use of additional oral prednisolone or intravenous medications. Analysis was by intention-to-treat. Results: There was no difference between groups for change in PRAM score at 24 hours (difference between means −0.39, 95% CI −0.84 to 0.06, p=0.09). Absolute PRAM score was lower in the prednisolone group at 4 hours (median (IQR) 1 (0–2) vs 2 (0–3), p=0.01) and 24 hours (0 (0–1) vs 0 (0–1), p=0.01), when symptoms had resolved for most children regardless of initial treatment. Admission rate, requirement for additional oral prednisolone and use of intravenous medication were lower in the prednisolone group, although there were no differences between groups for time taken to return to normal activities or rates of representation within 7 days. Conclusion: Oral prednisolone does not alter respiratory outcomes at 24 hours or beyond in preschool children presenting with acute wheeze.